6π, 8π and 10π Six Membered Sulfur Nitrogen Compounds: A Comparative Study with Organic Analogues. Issue 30 (8th August 2019) - De, Susmita; Sadik, Mohammad N. K.; Liya, Susan
Abstract: Benzene has played an important role in the development of the ideas concerning ′aromaticity′, as much as that benzene and its derivatives are the best examples of aromatic compounds. Although the inorganic aromatic compounds have been found to obey Hückel 4n+2 π electron rule, they often possess a different number of πe as compared to their organic analogues. One such system is cyclic compounds of S3 N3, where 10 π aromatic S3 N3 − and 8π S3 N3 + are known, but interestingly, a 6π benzene‐analogue of the sulfur‐nitrogen compound is not reported. Hence as a case study, we have undertaken an extensive theoretical investigation of the electronic structure of 6π, 8π and 10π electrons cyclic S3 N3 3+, S3 N3 + and S3 N3 −, based on the Energy Decomposition Analysis (EDA). We have also compared the results with isoelectronic classical C6 H6, C6 H6 2− and C6 H6 4− . Our results indicated that the π‐contribution increases and the σ‐contribution decreases, while the contribution from the orbital interaction energy remains nearly similar upon addition of π electrons to C6 H6 and S3 N3 3+ . However, the major decrease in the interaction energy is caused by the drastic reduction of the electrostatic component in C6 H6 4− and S3 N3 3+, which can be correlated to the instability of these molecules. Thus, aromatic binary compounds of sulfur and nitrogen are commonly π‐electron rich, while their aromatic hydrocarbon analogues are π‐electron precise. Abstract : The more the merrier: The aromatic binary compounds of sulfur and nitrogen are commonly π‐electron rich, while their aromatic hydrocarbon analogues are π‐electron precise. The stability of the 10π‐electron S3 N3 − can be mainly attributed to the increase in the electrostatic interaction as compared to 6π‐electron S3 N3 3+, whereas a reverse trend is observed for the hydrocarbon analogues.